Analisis Dampak Himbauan MUI Sumatera Barat terhadap Persepsi dan Preferensi Muzakki dalam Berzakat ke Baznas Bermasalah : Studi Kasus Baznas Kota Bukittinggi - Taufik Ramadhan; Aidil Alfin (Jurnal Multidisiplin Indonesia, 2026)
The advisory issued by the Indonesian Ulema Council (MUI) of West Sumatra in September 2024, recommending Muslims to withhold zakat from BAZNAS Bukittinggi City due to alleged politicization of zakat distribution, reflects the influence of religious authority on the economic behavior of the ummah. This study aims to analyze the impact of the advisory on muzakki’s perceptions and preferences in channeling zakat to BAZNAS Bukittinggi City. This research employed a qualitative field approach. Data were collected through observation, in-depth interviews with muzakki, BAZNAS administrators, and MUI West Sumatra representatives, as well as documentation. Data analysis used the Miles and Huberman model through data reduction, data display, and conclusion drawing, validated by source triangulation. The results show that the advisory influenced muzakki’s perceptions of BAZNAS credibility and governance, creating doubt and critical attitudes. Preference changes included reducing zakat contributions, switching to other zakat institutions, or distributing zakat directly to mustahik. These changes were influenced by trust in MUI, sharia concerns, zakat literacy, and institutional reputation. The study recommends strengthening BAZNAS transparency, accountability, and cooperation with MUI to restore muzakki trust.